Hubungan Nilai Ankle Brachial Index (Abi) Dengan Kualitas Hidup Penderita Diabetes Melitus Tipe 2 Di Persadia Cabang Kota Surakarta - Safitri, Liana; , Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2017)
Abstract Background. One of complications found in Diabetes Mellitus Type 2 affecting peripheral nerves is Peripheral Artery Disease (PAD). The disease is a condition in which lesions found in blood vessel are limiting arterial blood flow supplying extremities. The condition will cause blood vessel to be thickening and sclerotic easily triggering peripheral blood vessel disease. The condition can be detected by examining score of Ankle Brachial Index (ABI). PAD has been associated with reduced physical and functional capabilities. The condition has been causing decreased life quality of patient (Health Related Quality of Life) compared to cardiovascular diseases because of ill, sleep disturbance and reduced mobility. Diagnostic test of PAD with greater accuracy of ABI will likely to reflect changed quality of life of a person related to condition suffered. Purpose. Purpose of the research was to know relationship between ABI score and quality of life of patient with DM. Research Methods. The research was analytical (survey) one with cross-sectional approach. Sample of the research was 44 patients with DM type 2 in Persadia of Surakarta City branch. The sample was taken by using purposive sampling. Instruments of the research were questionnaire, sphygmomanometer and stethoscope. Bivariate result was obtained indicating that respondents with normal scores of ABI and good quality of life were 59.3% respondents and those with normal scores of ABI and less good quality of life were 35.3%. p value = 0.010 (p<0.05) meaning that Ha was accepted. Congclusion. Congclusion of the research showed that a relationship between score of ABI and quality of life of patient with DM type 2 in Persadia of Surakarta city branch was found. Key words: Diabetes mellitus, Ankle Brachial Index, Quality of life